2014
DOI: 10.1097/fbp.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Do the adjusting-delay and increasing-delay tasks measure the same construct

Abstract: Delay discounting describes the subjective devaluation of a reward when it is delayed. In animals, the adjusting- and increasing-delay tasks often are used to assess individual differences in, and drug effects on, delay discounting. No study to date, however, has compared systematically the measures of discounting produced in these tasks. The current study examined the correlation between measures of delay discounting derived from adjusting- and increasing-delay procedures. Twenty rats completed 30 sessions un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 75 publications
2
29
0
Order By: Relevance
“…1) suggests that both quantify the same underlying construct of impulsive choice in female rats. These findings extend a recent study by Craig et al (2014) who found the same positive correlation between these procedures, but in male rats. Indeed, related pigeon research has demonstrated that discounting rates determined via an adjusting-amount and -delay procedure were also positively correlated (Green et al 2007).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…1) suggests that both quantify the same underlying construct of impulsive choice in female rats. These findings extend a recent study by Craig et al (2014) who found the same positive correlation between these procedures, but in male rats. Indeed, related pigeon research has demonstrated that discounting rates determined via an adjusting-amount and -delay procedure were also positively correlated (Green et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…When combined, the present results suggest these impulsive choice procedures, each of which can assess the acute drug effects on impulsive choice in a single session, produce concordant measures of delay discounting rates in animals. As hypothesized by Craig et al (2014) and demonstrated in the present study, however, acute drug effects can produce conflicting results between these two choice procedures (see Stein and Madden 2013 for a review of issues).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…An additional 20 sessions were conducted following the correction of the programming error. Adjusting delays typically stabilize in 30 sessions or less (see, e.g., Craig, Maxfield, Stein, Renda, & Madden, 2014; Mazur, 2012) and have good test-retest reliability when assessed in a fixed number of sessions (McClure, Podos, & Richardson, 2014). Each rat's mean adjusted delay (MAD) over the final nine sessions served as the measure of delay discounting.…”
Section: Methodsmentioning
confidence: 99%